Partial and Radical Nephrectomy for Unilateral Synchronous Multifocal Renal Cortical Tumors - Mano, Roy; Kent, Matthew; Larish, Yaniv; Winer, Andrew G.; Chevinsky, Michael S.; Hakimi, Abraham Ari; Sternberg, Itay A.; Sjoberg, Daniel D.; Russo, Paul (Urology (Ridgewood, N.J.), 2015)
To evaluate clinicopathologic characteristics and treatment outcomes of patients undergoing partial nephrectomy (PN) or radical nephrectomy (RN) for unilateral synchronous multifocal renal tumors. We retrospectively reviewed medical records for 128 patients with nonmetastatic, unilateral, synchronous, multifocal renal tumors who underwent surgical resection at our institution from 1995 to 2012. Five patients with hereditary renal cell carcinoma were excluded. Differences between patient and tumor characteristics from the 2 nephrectomy groups were evaluated. Outcomes in terms of recurrence-free survival, overall survival, and chronic kidney disease upstaging were estimated using Kaplan-Meier methods. The log-rank test was used for group comparisons. The study cohort included 78 PN patients (63%) and 45 RN patients (37%); 17 of 95 planned PN (18%) were converted to RN. Tumor diameter and RENAL nephrometry scores were greater in RN patients (P <.0001 and P = .0002, respectively). Pathologic stage T3 was seen in 40% of RN patients and 10% of PN patients (P = .0002). Histologic concordance was apparent in 60 of 123 patients (49%). Median follow-up for patients alive without a recurrence was 4 years. Five-year recurrence-free survival was 98% for PN and 85% for RN. Five-year overall survival was 96% for PN and 86% for RN (P = .5). Five-year freedom from chronic kidney disease upstaging was 74% for PN and 55% for RN (P = .11). Partial nephrectomy for the treatment of unilateral, synchronous, multifocal, renal tumors with favorable characteristics was associated with a low recurrence rate. These findings suggest PN is an appropriate management strategy for this group of carefully selected patients.